2020
DOI: 10.1016/j.dib.2019.104777
|View full text |Cite
|
Sign up to set email alerts
|

Data on the effect of electrospinning parameters on the morphology of the nanofibrous poly(3-hydroxybutyrate-co-4-hydroxybutyrate) scaffolds

Abstract: Electrospinning is a promising approach to fabricate desirable electropsun nanofibrous scaffold that could be applied in the medical fields. In this study, bacterial copolymer poly(3-hydroxybutyrate-co-68 mol% 4-hydroxybutyrate) [P(3HB-co-68mol% 4HB)] copolymer produced was fabricated into electrospun nanofibers using various combination of electrospinning parameters including the polymer solution, applied voltage and injection speed. The morphology of the fabricated scaffolds were observed using scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The smooth, uniform and beadless P(3HB-co-4HB) nanofibers were fabricated after a careful optimization of the polymer solution concentration and processing parameters (applied voltage and flow rate). The final conditions were polymer concentration 8 wt%, applied voltage 25 kV and flow rate 1.5 mL/h, in agreement with those reported by Chai et al (2020). However, as already anticipated, these scaffolds lack biological cell recognition sites which restricts the cell-material interaction limiting their applications.…”
Section: Fabrication Of Nano-p(3hb-co-4hb) and Immobilization Of Biomimetic Rgd Peptidessupporting
confidence: 86%
“…The smooth, uniform and beadless P(3HB-co-4HB) nanofibers were fabricated after a careful optimization of the polymer solution concentration and processing parameters (applied voltage and flow rate). The final conditions were polymer concentration 8 wt%, applied voltage 25 kV and flow rate 1.5 mL/h, in agreement with those reported by Chai et al (2020). However, as already anticipated, these scaffolds lack biological cell recognition sites which restricts the cell-material interaction limiting their applications.…”
Section: Fabrication Of Nano-p(3hb-co-4hb) and Immobilization Of Biomimetic Rgd Peptidessupporting
confidence: 86%
“…Electrospinning at ambient conditions might have led to the observed differences as it was recently shown that variations in room temperature and/or differences in relative humidity can influence the surface structure of electrospun fibers . So far, P4HB has only been electrospun onto supporting membranes or in blends with other polymers. ,,, We thus believe that we were among the first to successfully electrospin P4HB into free-standing membranes. To achieve this, influencing parameters such as the polymer concentration, solvent systems and applied voltage, flow rate, and needle-to-collector distance were carefully adapted.…”
Section: Resultsmentioning
confidence: 91%
“…PHAs are biosynthesized by different bacterial species as natural energy storage of carbon compounds . Highly elastic properties (elongation at break of 1000%) combined with a tensile strength of 50 MPa make P4HB a promising candidate for various applications in the biomedical field such as sutures, hernia repair meshes, or scaffolds for plastic and reconstructive surgery. P4HB degrades into 4HB, which is a naturally occurring metabolite that enters the Krebs cycle and is eventually converted to water and carbon dioxide. , Despite its many advantages and reported use in clinical scenarios, limited knowledge is available on electrospun P4HB, which was mainly used as coating on, e.g., decellularized heart valves, microstents, or poly­(glycolic acid) meshes, , or electrospun as a copolymer with P3HB . Besides these reports, a patent from 2014 claims the production and use of ultrafine electrospun P4HB membranes for multiple biomedical applications; its implementation, however, remains open to date, and electrospun P4HB membranes have not been investigated as potential wound dressings.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to that the scaffolds were sterilized under UV (Spectrolinker™, XL-1000UV Cross linke, New York, NY, USA) at 1200 µJ/cm 2 for 30 min [ 12 ]. The cells viability and proliferation were assayed with MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium/PMS (phenazinmethosulfate) [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%